1986
DOI: 10.1104/pp.82.4.1151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wounding on Cytokinin Activity in Cucumber Cotyledons

Abstract: Three known physiological responses to exogenous cytokinins were measured in wounded and nonwounded cotyledons from cucumber (Cucumis sativus L. cv Marketer) seedlings grown in darkness. Enhanced cell division, chlorophyll formation, and cotyledon expansion were detected in wounded cotyledons. The data suggest that wounding enhances endogenous cytokinin activity.MATERIALS AND METHODS Plant Material. Cucumber (Cucumis sativus L. cv Marketer) seeds were surface sterilized by quickly rinsing in 1% (w:v) NaOCl, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Moreover, enhanced endogenous ABA, jasmonic acid, and ethylene production were detected (León et al 2001). Wounding also enhanced the endogenous cytokinin activity (Crane and Ross 1986;Iwase et al 2011). However, the hormonal response to excision seems to be completely different than to wounding.…”
Section: Explant Excision Resulting In Altered Endogenous Hormone Conmentioning
confidence: 98%
“…Moreover, enhanced endogenous ABA, jasmonic acid, and ethylene production were detected (León et al 2001). Wounding also enhanced the endogenous cytokinin activity (Crane and Ross 1986;Iwase et al 2011). However, the hormonal response to excision seems to be completely different than to wounding.…”
Section: Explant Excision Resulting In Altered Endogenous Hormone Conmentioning
confidence: 98%
“…Preliminary experiments indicated that treatment of intact seedlings with 50 #M BA was sufficient to stimulate dark growth of etiolated cucumber cotyledons as has been previously described [9,12] (Fig. 2).…”
Section: Regulation Of Phy Mrna In Response To Ba Treatmentmentioning
confidence: 99%
“…The levels were much lower in young leaves than in mature or senescent leaves. Cytokinins are thought to control greening [10,11,20] and aging of leaves [for review, see 12] and to mediate responses to wounding [7,14]. Thus, the expression of this gene could be closely related to the various actions of cytokinins.…”
Section: Introductionmentioning
confidence: 99%